FACTORS ASSOCIATED WITH THE INCIDENCE OF OCCUPATIONAL ACCIDENTS IN JANITORS AT RSU ROYAL PRIMA MEDAN YEAR 2023 - Gultom, Try Lasmarito; Munthe, Seri Asnawati (Akupun Tour Publisher, 2023)
Background: Work accidents can happen anywhere. One type of work that is prone to causing work accidents is janitors who work in hospitals. The risks faced by cleaning workers are exposure to biological factors and chemicals. Purpose: The aim of the research is what factors are related to work accidents at RSU Royal Prima Medan. Method: The research method uses quantitative methods, with a cross sectional design. The research population was all 45 cleaning staff at Royal Prima Hospital with a combination of two work shifts (morning and afternoon). The sampling technique in this research is total sampling. Data analysis uses univariate analysis, namely analysis carried out for each variable and bivariate analysis, namely analysis carried out on two variables. Results: The research results showed that there was a relationship between the use of personal protective equipment and the incidence of work accidents, namely (p-value = 0.000 <0.05), there was a relationship between the application of SOPs and the incidence of work accidents, namely (p-value = 0.000 < 0.05), there was The relationship between K3 training and the incidence of work accidents, namely (p-value = 0.000 <0.05). Disscusion and Conclusion: Thus, by implementing and providing protection and safety for workers, optimal productivity will be achieved, one of which is by conducting K3 training for each employee.